Demand for Money in Greece After Euro Area and Policy Uncertainties - Ongan, Serdar; Gocer, Ismet (Review of Economic Analysis, 2023)
This study examines the asymmetric effects of uncertainties in monetary policy on the demand for money in Greece. In doing so, it introduces and uses the monetary policy uncertainty (MPU) index, which can probably be a very appropriate and robust explanatory variable in demand-for-money models. Therefore, this study with this index differs from previous empirical studies that use conventional uncertainty-based independent variables. Empirical findings of both models indicate that changes in the MPU index have significant effects on Greek money demand. Additionally, compendious inferences of the nonlinear model for the Greek people’s financial preferences are as follow as: (i): Greek people invest more in alternative financial instruments and/or spend their money rather than hold (demand) it when the MPU index increases, (ii): Greek people’s money demand in both increases and decreases in the MPU index is predominantly determined by longer-term bond rate changes.